The Effectiveness of Global Positioning System in Tracking Services for Sustainable Road Haulage Operations - Adlan, Muhammad Akmal Asyraaf; Tarudin, Nur Farizan; Mohd Badrillah, Muhammad Izwan (ExcelingTech, 2020)
In today's highly competitive marketplace, businesses must innovate new ways to streamline their business and optimize productivity. With the aid of modern transport technology applications, it can create better visibility within the operation, which will enable more control over the business and stay ahead of the competition. Based on this scenario, the measurement of the effectiveness of tracking services by using the Global Positioning System (GPS) in improving the logistics of transporting goods was developed. Two indicators involved in this study, which are delivery time and fuel consumption. In gathering the data, researchers were conducting observation, monitoring and also a structured interview in Company XYZ focusing on the transport department. The highlights of the analysis are to evaluate the improvement of the delivery time and fuel consumption after implementing the GPS. This analysis has been carried out by assessing the trucking planning and managerial issues encountered by Company XYZ that already implement the GPS as a tracking method since the year 2016. This study is one of the information platforms for the logistics and transportation industry to grow and propel the country into a high-income economy based on the 11th Malaysia Plan [1].